Optimisation of product family design with consideration of supply risk and discount. (January 2016) - Luo, Xinggang; Li, Wei; Kwong, C.; Cao, Yan
Abstract Optimisation of product family design has been emphasised and studied for many years. However, previous studies only took overall cost or profit as an optimisation objective, but ignored the supply risk of a product family. Moreover, the discount associated with the bidding price, which is common in practice, was not considered in the modelling. In this paper, we propose a new multi-objective optimisation approach integrating supplier selection into product family design. In our optimisation model, not only the profit but also the supply risk of a product family is formulated as optimisation objectives. Consequently, we can evaluate and optimise a product family from many perspectives. In addition, as a bidding price discount may affect product family's configuration and supplier selection, we include linear piecewise discount of bidding prices from suppliers in our optimisation model. The NSGA-II algorithm is developed to achieve Pareto non-dominated solutions of the multi-objective optimisation model. Sensitivity analysis on the model parameters is performed, and several managerial insights for enterprises are achieved in the case study of a printing calculator product.